ENDOMETRIOSIS AND VTE: A REVIEW OF THE EVIDENCE AND PATHOPHYSIOLOGICAL MECHANISMS - Julia Dura; Julia Ciechanowicz; Stanisław Ciechanowicz; Marika Gutowska; Piotr Kupidłowski; Agata Nowacka; Adrianna Perzanowska; Aleksandra Przybylska; Zuzanna Tomaszewska; Anna Zielińska (International Journal of Innovative Technologies in Social Science, 2025)
Introduction and objective: Endometriosis is a chronic inflammatory condition affecting approximately 10% of women of reproductive age. Venous thromboembolism (VTE) is a major cause of mortality worldwide. Because the relationship between endometriosis and VTE is not well-defined, we conducted a review of studies that assessed the occurrence of VTE in women with endometriosis.Review methods: A structured PubMed search was conducted to identify studies published between January 2015 and April 2025 assessing the risk of VTE in patients with endometriosis. Seven studies met the inclusion criteria after screening for relevance and exclusion of case reports.Abbreviated description of the state of knowledge: Some large-scale studies suggest an elevated VTE risk in women with endometriosis, particularly in younger individuals, during pregnancy, or when using hormonal therapy. However, results vary due to differences in study design, diagnostic definitions, and confounder adjustment. Pathophysiologically, endometriosis-related inflammation, hormonal influences, and endothelial dysfunction may contribute to a prothrombotic state.Summary: The association between endometriosis and VTE remains unclear; biologically plausible mechanisms and clinical patterns suggest it may be relevant in certain populations. Future research should focus on well-characterized, prospective studies. Clinicians should remain alert to thrombotic risk in women with endometriosis, especially when additional risk factors are present.